(untitled) (Economics and region, 2021)
Searching for the optimal mechanism for the implementation of the construction project, which would provide both – the flexibility of the process and the maximum interaction of all stakeholders (investor/customer, designer, contractor), compliance with the budget and construction deadlines resulted to elaboration of a large number of alternative schemes for contract implementation and this article dedicated Design-Build scheme. DB contracts promote an integrated approach to construction and solve some problems faced by the construction industry today, for example, when the contractor is not responsible for design documentation developed by the design organization and often finds defects in design documentation that require additional time and considerable resources for correction.